Home Industry Tempe Factory One of the Community Solutions in Overcoming Rising Unemployment Rates in Kampung Lebak Pasar - Dwilana, Ady; Kamalludin, Kamalludin (Jurnal Pengabdian Nusantara, 2023)
This study aims to analyze how to develop a small tempe factory home industry in the context of poverty alleviation in Cigudeg village, Bogor district. By conducting product quality training, packaging selection, business analysis training, and business development. To overcome the weakness of limited manpower, more modern tools can be overcome, starting from production - distribution - marketing so that it is more effective and efficient. The target for this individual KKN activity plan is so that all people can enjoy a better life through the development of a home industry group system, so as to be able to increase people's income. Less skilled Human Resources are given special training for small business management which includes planning and organizing. Motivate the craftsmen for the business they are engaged in so that they can focus on developing their business to the fullest.